BJUI Knowledge: urology online learning resource. Issue 1 (8th December 2022) - Shaw, Greg; Lieblich, Aaron
Abstract : BJUI Knowledge is a useful resource not only for preparing for urology fellowship examinations but also to support ongoing professional development.